2012
DOI: 10.1097/01.pra.0000422740.87495.91
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the MMPI-2 Clinical, PSY-5, and RC Scales for Therapy Disruptive Behavior

Abstract: The information about the MMPI-2 obtained in this study may be helpful in case formulation when initiating inpatient treatment for patients with personality disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…However, Sellbom et al (2007) demonstrated that findings were relatively stronger when using the MMPI-2’s Restructured Clinical (RC) Scales, which were developed by Tellegen et al (2003) to address psychometric concerns with the Clinical Scales. The findings by Sellbom et al (2007) converge with prior research demonstrating that the RC Scales have improved psychometric features when compared with the Clinical Scales, particularly in terms of discriminant validity (Arbisi, Sellbom, & Ben-Porath, 2008; Ben-Porath & Tellegen, 2008; Forbey & Ben-Porath, 2007; Handel & Archer, 2008; McCord & Drerup, 2011; Scholte et al, 2012; Sellbom, Ben-Porath, Baum, Erez, & Gregory, 2008; Sellbom, Ben-Porath, & Graham, 2006; Sellbom, Graham, & Schenk, 2006; Wallace & Liljequist, 2005; Wygant et al, 2007).…”
supporting
confidence: 76%
“…However, Sellbom et al (2007) demonstrated that findings were relatively stronger when using the MMPI-2’s Restructured Clinical (RC) Scales, which were developed by Tellegen et al (2003) to address psychometric concerns with the Clinical Scales. The findings by Sellbom et al (2007) converge with prior research demonstrating that the RC Scales have improved psychometric features when compared with the Clinical Scales, particularly in terms of discriminant validity (Arbisi, Sellbom, & Ben-Porath, 2008; Ben-Porath & Tellegen, 2008; Forbey & Ben-Porath, 2007; Handel & Archer, 2008; McCord & Drerup, 2011; Scholte et al, 2012; Sellbom, Ben-Porath, Baum, Erez, & Gregory, 2008; Sellbom, Ben-Porath, & Graham, 2006; Sellbom, Graham, & Schenk, 2006; Wallace & Liljequist, 2005; Wygant et al, 2007).…”
supporting
confidence: 76%
“…Several studies have examined the utility of the MMPI-2-RF scales in predicting various therapy-disruptive behaviors. For instance, Scholte et al (2012a) studied 106 patients with personality disorders who were undergoing treatment and found that Antisocial Behavior (RC4), Disconstraint-Revised (DISC-r), and RC2, as well as low scores on RC7, were associated with inappropriate anger outbursts, impulsive acts, parasuicidal behavior, and contact violations. Scholte et al (2012b) followed up with 179 patients who had undergone treatment and found that RC2 and RC8 predicted lesser symptomatic improvement over time.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Specifically, its anchoring Restructured Clinical (RC) scales have no item overlap and their internal consistency was optimized (among other psychometric improvements; Tellegen et al, 2003). Reflecting the success of this effort, several studies demonstrate that the RC Scale scores have better reliability and validity than the original Clinical Scales (Arbisi, Sellbom, & Ben-Porath, 2008; Forbey & Ben-Porath, 2007; Handel & Archer, 2008; McCord & Drerup, 2011; Scholte et al, 2012; Sellbom, Ben-Porath, & Stafford, 2007; Wygant et al, 2007).…”
mentioning
confidence: 99%